Influence of microbiological quality of drinking water in the intestinal morphology of broilers - Amoroso, Lizandra [UNESP]; Baraldi-Artoni, Silvana M. [UNESP]; Soares, Nilce M.; Pinto, Fernanda R.; Pacheco, Maria R. [UNESP]; Sagula, Alex L. [UNESP]; Rios Alva, Juan Carlos [UNESP]; Amoroso, Patricia (Revista Pesquisa Veterinaria Brasileira, 2015)
To evaluate if microbiological quality of drinking water has an effect on intestinal morphology of broilers, the weekly water consumption by them was verified, and microbiological analysis of water samples, scanning electron microscopy and small intestine histology of broilers treated with filtered and not filtered water was conducted. Chickens that ingested filtered water had access to fewer fecal microorganisms (2.52 +/- 0.99 Most Probable Number MPN of fecal coliforms and 1.17 +/- 1.25 MPN of Escherichia coli) compared to those who drank no filtered water (3.62 +/- 0.67 and 2.53 +/- 1.13 MPN). At 14, 21 and 45 days old, the duodenum, jejunum and ileum of 96 birds were sampled. After laboratory routine, samples preserved in glutaraldehyde were eletronmicrographed and evaluated by villous density, and the material maintained in Bouin's solution was destinated to histological slides that were analyzed morphometrically. The duodenum of birds that ingested not filtered water had the highest density of villi in response to microbiological water quality. In intestinal morphometry, were observed that birds receiving not filtered water showed increase in intestinal crypts depth and presented larger villi compared with birds that ingested filtered water. It is cocluded that filtered water, offered to broilers in a life span of 45 days, favors the maintenance of intestinal integrity.

Para avaliar se a qualidade microbiológica da água de dessedentação intervém na morfologia intestinal de frangos de corte, foram analisados o consumo semanal de água, a microbiologia de amostras de água, a microscopia eletrônica de varredura e a histologia do intestino delgado de frangos de corte tratados com água filtrada e não filtrada. Os frangos que ingeriram água filtrada tiveram acesso ao menor número de micro-organismos fecais (2,52±0,99 Número Mais Provável (NMP) de coliformes fecais e 1,17±1,25 NMP de Escherichia coli) em relação aos que ingeriram água não filtrada (3,62±0,67 NMP e 2,53±1,13 NMP). Aos 14, 21 e 45 dias de vida, foram colhidas amostras do duodeno, jejuno e íleo de 96 aves. Após rotina laboratorial, as amostras conservadas em glutaraldeído foram eletronmicrografadas e analisadas quanto à densidade de vilos e o material mantido em solução de Bouin foi destinado à confecção de lâminas histológicas que foram analisadas morfometricamente. O duodeno das aves que receberam água não filtrada apresentou maior densidade dos vilos em resposta à qualidade microbiológica da água. Na morfometria intestinal, observou-se que aves que receberam água não filtrada apresentaram aumento na profundidade das criptas intestinais e elevada altura das vilosidades em relação às aves que ingeriram água filtrada. Infere-se que a água filtrada, oferecida aos frangos de corte em um período de vida de 45 dias, favorece a manutenção da integridade intestinal.
Influência da qualidade microbiológica da água de dessedentação na morfologia intestinal de frangos de corte
Keywords: Water quality; Filtered water; Birds; Broilers; Intestinal integrity; Scanning electron microscopy; Qualidade da água; Água filtrada; Aves; Frangos de corte; Integridade intestinal; Microscopia eletrônica de varredura